Increasing adiposity and metabolic dysfunction prolong QTc interval and increase risk of ventricular arrhythmias: results from the UK Biobank. (24th May 2021) - Patel, K; Li, X; Xu, X; Sun, L; Ardissino, M; Punjabi, P; Purkayastha, S; Peters, N; Ware, J; Ng, FS
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): National Institute for Health Research Background/purpose: Small-scale studies have associated obesity and metabolic ill-health with QTc interval prolongation. Whether these associations are modulated by an underlying genetic predilection and translate into higher risks of ventricular arrhythmias (VA) is unknown. Methods:  Using the UK Biobank and adjusted multivariate regression analysis, we studied the associations between QTc and clinical measures of adiposity and metabolic ill-health. A polygenic risk score was used to determine whether these associations are modulated by a genetic predilection for QTc prolongation. We compared QTc between four clinical phenotypes defined according to presence (+) or absence (-) of obesity (Ob), and metabolic ill-health (MU). Logistic regression was used to calculate odds ratios (OR) for VA amongst these groups. Results:  23, 683 individuals (11, 563 male, mean age 61.0 + 7.5years) had ECG and clinical data available. QTc prolongs with increasing body mass index (0.76ms/kg/m2, 95%CI: 0.68-0.83ms/kg/m2), body fat (0.45ms/%, 95%CI:0.39-0.50ms/%), hip girth (0.35ms/cm, 95%CI:0.31-0.39ms/cm) and waist girth (0.32ms/cm, 95%CI:0.29-0.35ms/cm); all p < 0.001. Genetically determined repolarisation reserve has no significant modulatory effect on the QTc-prolonging effects of increasing adiposity. Referenced to Ob-MU-, Ob + MU- and Ob-MU+ independently prolong QTc to a comparable extent, and Ob + MU+ has an additive effect on QTc prolongation. With reference to Ob-MU-, OR for VA in Ob-MU+ males and females were 5.96 (95%CI:4.70-7.55) and 5.10 (95%CI:3.34-7.80), respectively. OR for Ob + MU+ were 6.99 (95%CI:5.72-8.54) and 3.56 (95%CI:2.66-4.77) in males and females, respectively, (all p < 0.001, see Table). Conclusion:  Adiposity and metabolic perturbation prolong QTc to a similar extent, and their co-existence exerts an additive effect. These effects are independent of genetically determined repolarisation reserve. Despite their comparable QTc prolonging effects, metabolic ill-health is associated with higher OR for VA than obesity.